Proceso de atención de enfermería en paciente de sexo masculino de 48 años de edad con shock cardiogenico. - Estrada Estrella, Juana Yajaira (2020)
The process of nursing care in a 48-year-old male patient with cardiogenic shock is presented below. Being one of the patologices with the highest percentages of mortality in patients with diabetic and hypertensive antecedents, it is a very important topic to carry out a case study, since the nurse is in charge of providing primary and direct care to the patient, where he fulfills the role of managing all cardiological devices, and respirators to maintain mechanical ventilation if warranted. Therefore, we will carry out a process of nursing care in patients with cardiogenic shock, to assess them clinically in all their affectations, giving them adequate care for the recovery of their health, based on different nursing theories.